De l’ajustement à la transformation : vers un essor de l’adaptation ? - Guillaume Simonet (Développement Durable et Territoires)
The 2014 report of the Intergovernmental Panel on Climate Change confirms the rise of the notion of adaptation by devoting a prominent place. Among the dozen of new definitions, the “transformational adaptation” appears to be the most innovative. Indeed, the need for a transformation of the workings of the socio-economic system at territorial scale is now inevitable rather than just some adjustments. The article questions this new definition by showing the contribution of social and human sciences and the opportunities offered in terms of planning, interdisciplinary research and conceptualization.